On some new sequence spaces defined by Orlicz functions - Esi, A; Isik, M; Esi, A (Indian Nat Sci Acad, 2004)
In this paper we introduce some new sequence spaces using Orlicz function. We also examine some properties of these sequence spaces.
Keywords: sequence space; Orlicz function; invariant mean